EXPLORING THE LEGALITY OF AI IN CUSTOMS PROCEDURES - Andrei-Alexandru STOICA; Aurel Ștefan PICA (Challenges of the Knowledge Society)
This paper explores the complex interaction between AI and customs procedures, aiming to uncover the legal ramifications associated with the integration of AI technologies in this field. With the rapid advancement of AI, customs authorities worldwide are increasingly adopting automated systems to improve the efficiency, accuracy, and security of cross-border trade operations. However, as AI systems take on significant roles in decision-making processes traditionally overseen by humans, concerns regarding legality, accountability, and transparency become prominent. Through a thorough examination of existing legal frameworks, international agreements, and relevant case law related to AI implementation in customs procedures, this research conducts a comprehensive analysis. It seeks to shed light on the evolving legal landscape surrounding AI in customs operations through a comparative study of various regulatory approaches and interpretations. Additionally, the paper scrutinises emerging ethical considerations and policy challenges arising from AI adoption, emphasising the necessity for coherent legal frameworks that uphold fundamental rights while promoting innovation and facilitating trade. By synthesising legal, ethical, and practical viewpoints, this study contributes to a nuanced comprehension of the intricate dynamics influencing the legality of artificial intelligence in customs procedures.